#GER@ÇÕES: entre baby boomers, X e Y e seus (des)encontros nas relações de trabalho no Ministério Público da Paraíba - Pinto, Graziela Tomaz Benevenuto (2018)
The (re) evolution of science and technology that the network society is based on has led to political, economic and sociocultural transformations that surpass the emerging markets and the effectiveness of public services. Furthermore, it (re) dimensions new professional parameters that, in the digital culture, promote and intensify interaction between the generations in the labor market. Presently, organizations consist of social subjects that belong to different historical phases, whose repercussions require that organizational actions are taken in accordance with a strategic human resources management. Therefore, the present research analyzed the (dis) harmony between Baby boomers, generations X and Y with respect to the work relationships and its intricacies in regard to the organizational environment of the D.A Office of Paraíba (Ministério Público da Paraíba/MPPB). This field research is based on a descriptive and quantitative approach, whose data was collected through a closed-ended questionnaire that consisted of 28 questions. It was administered to a stratified proportional sample of 209 members and servants, out of 509 individuals that work at the D.A Office of Paraíba, from the capital city and other D.A Offices across the state of Paraíba. The research construct in regard to data collection and analysis was based on three different scales: a) the scale of affective organizational commitment; b) the scale of satisfaction; and c) the scale of intention to stay in the organization. The results were decoded through a software called SPSS and the fundamentals of descriptive statistics were used. In addition, inferential statistics was used in order to carry out Chi-Square tests, t-tests and Spearman Correlation. The results showed that the subjects had a high organizational commitment and a firm intention to stay in the D.A Office of Paraíba, regardless of their generation. However, as far as job satisfaction is concerned, Baby boomers seemed more satisfied with their work in the D.A Office of Paraíba than those from generations X and Y. This very study observed that there is more harmony than disharmony in regard to behaviour between the generations under analysis and proposed the implementation of Strategic Human Resources Management policies in the D.A Office of Paraíba, stressing individual competences of its members and servants in order to share integrated actions in terms of experiences and challenges, with solidarity, understanding and mutual learning between these generations.